The World Wars through tabletop wargaming: An innovative approach to university history teaching. (October 2015) - Reynaud, Daniel; Northcote, Maria
This article explores the experiences of a lecturer and students in a class on the World Wars, where wargaming is used alongside traditional lecturing as a learning experience. It outlines the processes used and then evaluates the various kinds of learning, historical and other, that occur. Drawing on literature associated with history education approaches, authentic learning, reflective practice, slow pedagogy and productive failure, the study's methods track the students' learning experiences across a semester in which they engage in a mixture of traditional learning experiences and authentic wargaming sessions. The paper concludes with the strengths and weaknesses of wargaming as a form of history pedagogy.